Measuring Behaviors of Individual Adolescents during Group-Based Substance Abuse Intervention. Issue 4 (October 2014) - Stein, L. A. R.; Clair, Mary; Martin, Rosemarie A.; Soenksen, Shayna; Lebeau, Rebecca; Rohsenow, Damaris J.; Kahler, Christopher W.; Hurlbut, Warren; Monti, Peter M.
Background: Group treatment is delivered in youth correctional facilities, yet groups may be iatrogenic. Few measures with demonstrated psychometric properties exist to track behaviors of individuals during groups. The authors assessed psychometrics for the Group Process—Individual Level measure (GP-IL) of group treatment. Methods: N = 152 teens were randomized to 1 of 2 groups (10 sessions each). Adolescents, counselors, and observers rated teen behaviors at sessions 3 and 10. GP-IL assesses reinforcement for deviancy and positive behaviors, member rejection, and counselor connection and praise. Results: Internal consistency and 1-month stability were demonstrated. Concurrent validity is supported by correlations with measures expected to be associated with group behavior (e.g., coping skills). Counselors and observers rated more deviancy during interactive skills-building groups versus didactic psychoeducational groups ( P ≤ .005). Scales evidenced incremental validity. Conclusions: GP-IL offers a sound method of tracking adolescent behaviors for professionals working with groups. Counselors ratings were most reliable and valid overall.